E-023 Patient Outcomes, Aneurysm Occlusion, and Cerebral Infarction Following Endovascular Treatment of Dissecting Vertebral Artery Aneurysms. (29th July 2016) - Heit, J; Dodd, R; Do, H; Steinberg, G; Chang, S; Marks, M
Abstract : Introduction: Subarachnoid hemorrhage (SAH) secondary to rupture of an intradural dissecting vertebral artery aneurysm (DVAA) results in significant morbidity and mortality. Prior studies suggest favorable outcomes following endovascular treatment of ruptured DVAA by parent vessel occlusion or stent-assisted coil embolization, but post-procedural cerebral infarction related to endovascular treatment is less well characterized. We determined patient outcomes and cerebral infarction following endovascular treatment of ruptured DVAA. Materials and methods: We retrospectively reviewed all consecutively patients presenting to our neurovascular referral center over a 10 year period with with SAH due to a ruptured DVAA. Patient demographic, treatment, and outcome data were determined from the medical record. DSA, CT, and MRI studies were reviewed for DVAA characteristics and cerebral infarction. Results: Ruptured DVAA were identified in 30 patients with an average age of 56 years (range 35–86 years). DVAA affected the right vertebral artery in 20 patients (67%; p = 0.2), the non-dominant vertebral artery in 18 patients (60%; p = 0.4). Parent vessel occlusion was performed in 25 patients, stent-assisted coiling in 4 patients, and flow diversion in 1 patient. Aneurysm occlusion was achieved in 27 patients (90%). Symptomatic vasospasm requiring endovascular treatment occurred in 12 patients (35%). Cerebral infarction occurred in 9 patients (30%) following endovascular treatment, which were secondary to vasospasm in 5 patients (56%), parent vessel occlusion in 2 patients (22%), and a combination of vasospasm and parent vessel occlusion in 2 patients (22%). No other complications were identified. 8 patients (27%) had a good clinical outcome (mRS 2) at discharge, which increased to 18 patients (60%) at 3 months of follow-up. 5 patients (17%) died as a result of their ruptured DVAA. Presenting Hunt and Hess scale greater than 3 ( p = 0.003) was associated with a poor clinical outcome (mRS > 2 or death). Patient sex, age, hypertension, hyperlipidemia, diabetes, coronary artery disease, smoking, illicit drug use, alcohol abuse, a family history of aneurysms, presenting Fisher grade, and the development of vasospasm requiring endovascular treatment did not correlate with clinical outcome. Conclusions: Endovascular DVVA treatment results in a high rate of aneurysm occlusion and good clinical outcome in a majority of patients. The rate of cerebral infarction related to endovascular parent vessel occlusion is high. Further studies should determine if ruptured DVVA treatment by flow diversion results in acceptable rates of aneurysm occlusion and lower rates of post-treatment cerebral infarction compared to endovascular parent vessel occlusion. Disclosures: J. Heit: None. R. Dodd: None. H. Do: None. G. Steinberg: None. S. Chang: None. M. Marks: None.